Effect of Human Factor on Fear and Stress Reactions and Some Performance Parameters in Broiler Chickens - Turkyilmaz, Mehmet Kenan; Nazligul, Ahmet; Balkaya, Muharrem; Dereli, Evrim Fidan (International Journal of Poultry Science, 2009)
The aim of the study was to investigate the effects of visual human contacts on fear and stress reactions and some performance parameters in broiler chickens. A total of 180 (Ross-308), day-old commercial broiler chicks allocated into 3 groups each containing 60 chicks. Birds in Group-I and Group-II were exposed to regular visual contact for 5 min for two and three times a day while control counterparts had no visual contact during the study (1-37 days). Tonic Immobility (TI) duration and Heterophil to Lymphocyte Ratio (HLR) parameters were used to determine the level of fear and stress, respectively. The Newcastle disease antibody titres were analysed by using a commercial ELISA kit. The results revealed that visual human contact has no significant effect on tonic immobility duration and the number of induction in broiler chickens. This study also showed that visual human contact has no effect on parameters such as body weight, feed intake, feed conversion ratio, mortality and immunisation in broilers.